2004
DOI: 10.1523/jneurosci.0713-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Abnormalities in the Brains of Human Subjects Who Use Methamphetamine

Abstract: We visualize, for the first time, the profile of structural deficits in the human brain associated with chronic methamphetamine (MA) abuse. Studies of human subjects who have used MA chronically have revealed deficits in dopaminergic and serotonergic systems and cerebral metabolic abnormalities. Using magnetic resonance imaging (MRI) and new computational brain-mapping techniques, we determined the pattern of structural brain alterations associated with chronic MA abuse in human subjects and related these defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
522
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(571 citation statements)
references
References 64 publications
25
522
12
Order By: Relevance
“…Furthermore, both HD groups demonstrated a similar frequency of previous substance dependence, which primarily involved cocaine, methamphetamine, and cannabis. Chronic misuse of these substances has been reported to adversely affect human brain morphology in active and recently detoxified abusers (e.g., Bartzokis et al, 2000;Matochik et al, 2005;O'Neill et al, 2001;Thompson et al, 2004). The long-term, enduring effects of cocaine, methamphetamine, or cannabis on human brain morphology are largely unknown, especially when dependence is in long-term sustained full remission.…”
Section: Potential Mechanisms For Neocortical Gm Dysmorphology In Conmentioning
confidence: 99%
“…Furthermore, both HD groups demonstrated a similar frequency of previous substance dependence, which primarily involved cocaine, methamphetamine, and cannabis. Chronic misuse of these substances has been reported to adversely affect human brain morphology in active and recently detoxified abusers (e.g., Bartzokis et al, 2000;Matochik et al, 2005;O'Neill et al, 2001;Thompson et al, 2004). The long-term, enduring effects of cocaine, methamphetamine, or cannabis on human brain morphology are largely unknown, especially when dependence is in long-term sustained full remission.…”
Section: Potential Mechanisms For Neocortical Gm Dysmorphology In Conmentioning
confidence: 99%
“…For example, studies have shown extensive reductions in the density and activity of DAT in the striatum in the days following MA use (Chang et al, 2007). Imaging studies have also shown that hypoactivity in the striatum can be correlated with self-reports of depression and anxiety in recovering MA users (Thompson et al, 2004). In addition, cognitive dysfunction and decreased activity of DA receptors caused by prolonged MA use can contribute to poor impulse control and inability to maintain goal-related behavior (Monterosso et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is only in the last decade, however, that researchers have examined the effects of methamphetamine on the human brain. For example, the neurobiological abnormalities associated with long-term, high-dose methamphetamine exposure have been described using various neuroimaging 25 and electrophysiological 6 techniques. The functional consequences of long-term, high-dose methamphetamine exposure are also reasonably well-established, and include marked deficits on measures of episodic memory.…”
mentioning
confidence: 99%
“…2 In another study of 22 subjects, high-resolution MRI revealed that reduced hippocampal volume was associated with poorer performance on a memory test that was constructed specifically for use in that laboratory. 5 …”
mentioning
confidence: 99%